Characteristics and Drivers of Marine Heatwaves in the Western Equatorial Indian Ocean. Issue 10 (14th October 2022) - Qi, Ruisi; Zhang, Ying; Du, Yan; Feng, Ming
Abstract: The spatio‐temporal characteristics of the interannual variability and long‐term trend of the marine heatwaves (MHWs) and related dynamic mechanisms in the western equatorial Indian Ocean (WEIO) are investigated using satellite observations. A prominent MHW hot spot is found in a region of the WEIO (48°E−54°E, 2°S–2°N), with a mean MHWs' intensity, duration, and frequency of 1.54°C, 13.33 days, and 1.97 times, respectively. MHWs in the hot spot region have significant interannual variability after removing the long‐term trend, associated with Indo‐Pacific major climate modes. In 1982/1983, 1983/1984, 1987/1988, 1997/1998, 2006/2007, 2009/2010, 2011/2012, 2012/2013, 2014/2015, 2015/2016, and 2019/2020, the MHWs occurred with longer duration, higher frequency, and more total days. These years correspond to a positive Indian Ocean Dipole, or an El Niño event, or both. The occurrence of MHWs accompanied by anomalous positive sea surface height suggests that oceanic planetary wave processes modulate MHWs in the WEIO. Westward‐propagating downwelling equatorial Rossby waves triggered by anomalous equatorial easterly winds drive the convergence of warm upper‐ocean water and weaken the upwelling of cool subsurface water, which favor anomalously warm sea surface temperature (SST) and the occurrence of MHWs. In addition, the westward‐propagating off‐equatorial downwelling Rossby waves in the southern tropical Indian Ocean also affect MHWs in the WEIO through the propagation and reflection of waves. The annual MHW frequency, duration, and total days in the hot spot region increase up to 1.56 times, 4.95 days, and 31.72 days per decade, respectively, related to the significant increase in mean SST under global warming. Plain Language Summary: Marine heatwaves (MHWs) are anomalous warming events in the ocean that can be disastrous for the global marine ecosystem and lead to local socioeconomic losses. The western equatorial Indian Ocean (WEIO), as the western pole of the Indian Ocean Dipole (IOD) and the upwelling region where the Indian Ocean monsoon prevails, experiences strong MHWs. This study shows the characteristics and dynamic mechanisms of MHWs in the WEIO. The MHWs had a significant interannual variability during 1982–2020, associated with the positive IOD and El Niño events. It was found that oceanic planetary wave processes cause the occurrence of MHWs in the WEIO. Westward‐propagating downwelling equatorial Rossby waves and off‐equatorial downwelling Rossby waves in the southern tropical Indian Ocean increase sea surface temperature in the WEIO by suppressing upwelling and entrainment. Under global warming, increasing frequency, duration, and annual days of MHWs are found in the WEIO. Global warming is consistently one of the main causes of extreme warm events. Understanding the characteristics and mechanisms that drive the occurrence of MHWs in the WEIO is a step toward predicting these extreme events. Key Points: Marine heatwaves in the western equatorial Indian Ocean (WEIO) have significant interannual variability related to the Indo‐Pacific climate Marine heatwaves in the WEIO are mainly driven by westward‐propagating downwelling equatorial Rossby waves and off‐equatorial Rossby waves The frequency and duration of marine heatwaves exhibited significant increasing trends in the WEIO from 1982 to 2020